Establishment of a human three-dimensional chip-based chondro-synovial coculture joint model for reciprocal cross talk studies in arthritis research. Issue 21 (10th September 2021) - Rothbauer, Mario; Byrne, Ruth A.; Schobesberger, Silvia; Olmos Calvo, Isabel; Fischer, Anita; Reihs, Eva I.; Spitz, Sarah; Bachmann, Barbara; Sevelda, Florian; Holinka, Johannes; Holnthoner, Wolfgang; Redl, Heinz; et al.
Abstract : In the current study we have developed a chondro-synovial joint-on-a-chip model that comprises of hydrogel-based human synovial and cartilage organoids for arthritic tissue cross-talk studies. Abstract : Rheumatoid arthritis is characterised by a progressive, intermittent inflammation at the synovial membrane, which ultimately leads to the destruction of the synovial joint. The synovial membrane as the joint capsule's inner layer is lined with fibroblast-like synoviocytes that are the key player supporting persistent arthritis leading to bone erosion and cartilage destruction. While microfluidic models that model molecular aspects of bone erosion between bone-derived cells and synoviocytes have been established, RA's synovial-chondral axis has not yet been realised using a microfluidic 3D model based on human patient in vitro cultures. Consequently, we established a chip-based three-dimensional tissue coculture model that simulates the reciprocal cross talk between individual synovial and chondral organoids. When co-cultivated with synovial organoids, we could demonstrate that chondral organoids induce a higher degree of cartilage physiology and architecture and show differential cytokine response compared to their respective monocultures highlighting the importance of reciprocal tissue-level cross talk in the modelling of arthritic diseases.